Peranan Efektivitas Faktor-Faktor yang Mempengaruhi Relationship Marketing Produk Air Mineral Aqua di Surabaya - Nuryanto Nuryanto (BIP's JURNAL BISNIS PERSPEKTIF, 2011)
This research is to analyse the strategy to increase the effectivity of relationshipmarketing among the firm and its retailers. The effectivity of relationshipmarketing is very important in recent years. The result of the research based onthe case of AQUA brand shows that relationship marketing is influenced by thetruth and cooperation. This research also describes the factors developing thevariables of truth and cooperation.